Comparing Efficiency of Rice Washing and Soaking Processes in Reducing the Amount of Aflatoxin B1 - Hamidreza Nassehinia; Mehdi Kiani; Zaher Khazaei; Hasan Torabi; Malihe Sohrabivafa; Reza Beiranvand; Sajjad Rahimi Pordanjani (Iranian Journal of Health, Safety and Environment, 2017)
Contamination of some agricultural products by mycotoxins has exposed the human and animal health to serious concerns. Aflatoxin B1 is the most toxic type of aflatoxins, which is of the highest amount in different foods, including rice, among various types of aflatoxins. The present study was aimed to evaluate the amount of this toxicant in the consuming rice in Yazd city and investigate the effect of rice washing and soaking process on reduction of the mean concentration of aflatoxin B1. The present study was a descriptive-analytical one, in which 36 rice samples (18 domestic types and 18 foreign types of rice) were randomly selected from the rice distribution centers in Yazd city. The Standard No.6872 of the Institute of Standards & Industrial Research of Iran (ISIRI) was used for measuring the amount of aflatoxin B and G toxicants using HPLC (high pressure or performance liquid chromatography) method and purifying by immune affinity column. Analysis of the collected data was performed using SPSS-22 statistical software as well as the statistical methods of one-way ANOVA and Tukey HSD. The mean concentration of aflatoxin B1 in domestic and imported rice was measured equal to 1.461 and 0.508ng/g, respectively. The contamination rate in the imported rice was lower than that in the domestic one, while there was no significant relationship between them (p≥0.166); furthermore, the effect of soaking process on reduction of the toxicant amount in one and ten hours of soaking was statistically insignificant. There was no significant relationship between the effect of a single time of washing and reduction of the amount of toxicant; however, in case of three and five times of washing, the amount of toxicant exhibited a reduction of 68.2% and 98.7%, respectively, which was statistically significant (p